The improved hydrodechlorination catalytic reactions by concerted efforts of ionic liquid and activated carbon support. (10th April 2019) - Li, Rongrong; Zhou, Zehua; Chen, Jingjing; Wang, Shiting; Zheng, Jianli; Chu, Chu; Zhao, Jia; Fan, Huajun; Han, Deman
Abstract : Modified and stabilized palladium nanoparticles were prepared successfully by using an ionic liquid, 1-butyl-3-methylimidazolium trifluoroacetate. Abstract : Modified and stabilized palladium nanoparticles were prepared successfully by using an ionic liquid, 1-butyl-3-methylimidazolium trifluoroacetate. Activated carbon was used as a support for the palladium catalyst. Instead of using hydrogen gas, the Pd-catalyzed hydrodechlorination (HDC) reaction in this study used aqueous formic acid–formate buffer solutions as a hydrogen source due to its non-flammability. The results showed that both the ionic liquid and active carbon support facilitate the Pd active center to effectively carry out the catalytic HDC reaction of 4-chlorophenol (4-CP). The ionic liquid (IL) played a dual role as both a solvent and co-factor to facilitate the reaction. The IL would stabilize, better disperse, and prevent the congregation of palladium nanoparticles. On the other hand, active carbon provides a stronger binding site for stabilizing the active Pd centers. The catalytic HDC reaction indicated that the turn over frequency (TOF) of ionic liquid with a reduced catalyst was about 5–6 times higher than that of the non-ionic liquid mediated catalyst. This excellent catalytic activity suggested that the ionic liquid is dispersing nanoparticles effectively, preventing the creation of Pd nanoparticle clusters through the strong interaction of Pd species with the ionic liquid (IL). This IL-Pd interaction helped to form a protection layer to stabilize the Pd active centers. This study also confirmed that both the Pd 0 and Pd n + states were required for the catalytic HDC reaction. Furthermore, the Pd-catalyst was characterized by different techniques such as Brunauer–Emmett–Teller (BET) surface area analysis, X-ray photoelectron spectroscopy, transmission electron microscopy (TEM) and Fourier-transform infrared spectroscopy (FT-IR).